Interpretation of Secondary Instruments in International Law (Polish Yearbook of International Law, 2016)
This article explores the legal principles that govern the interpretation of “secondary instruments” in international law. A “secondary instrument” under international law is, for the purposes of this article, a written document adopted by a body empowered by a treaty to take action with respect to the treaty, but which is not itself a treaty. Such instruments find increasing application in international law. The article specifically examines the interpretation of secondary instruments arising in five settings in international practice: the United Nations Security Council, the International Maritime Organization, the International Seabed Authority, the International Whaling Commission, and conferences/meetings of the parties under multilateral treaties. This selection of practice will serve to illustrate principles of interpretation across a range of international institutional settings for the purpose of determining the rights and obligations of state-parties to a treaty regime.